2016
DOI: 10.1158/0008-5472.can-15-1846
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Loss of DUSP4 Contributes to the Progression of Intraepithelial Neoplasm of Pancreas to Invasive Carcinoma

Abstract: The progression from precursor lesions of pancreatic cancer, including pancreatic intraepithelial neoplasia and intraductal papillary mucinous neoplasm (IPMN), to invasive disease is characterized by stepwise accumulation of genetic alterations. However, it remains unclear whether additional alterations are required for the progression of high-grade neoplasms to invasive pancreatic carcinoma. We compared the genomic profiles of paired noninvasive and invasive carcinoma tissues collected from patients with IPMN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 45 publications
5
55
0
Order By: Relevance
“…For immunohistochemistry, rabbit polyclonal antisera was raised against synthetic peptides corresponding to the amino terminal sequences of human DUSP4 (NH 2 ‐VHSAPSSLPYLHSP‐COOH), and purified by affinity chromatography (Unitech, Chiba, Japan). The specificity of antisera against DUSP4 was confirmed by both immunocytochemistry and Western blot analysis using pancreatic cancer cell lines, PANC‐1 stably re‐expressing DUSP4 (PANC‐1/DUSP4‐1) and PANC‐1 expressing only the blasticidin resistance gene (PANC‐1/cont) …”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…For immunohistochemistry, rabbit polyclonal antisera was raised against synthetic peptides corresponding to the amino terminal sequences of human DUSP4 (NH 2 ‐VHSAPSSLPYLHSP‐COOH), and purified by affinity chromatography (Unitech, Chiba, Japan). The specificity of antisera against DUSP4 was confirmed by both immunocytochemistry and Western blot analysis using pancreatic cancer cell lines, PANC‐1 stably re‐expressing DUSP4 (PANC‐1/DUSP4‐1) and PANC‐1 expressing only the blasticidin resistance gene (PANC‐1/cont) …”
Section: Methodsmentioning
confidence: 88%
“…Western blot analysis was carried out as described previously, with some modifications. Briefly, cultured cells were lysed in SDS‐modified RIPA buffer (0.1% w/v SDS, 40 mmol L −1 HEPES‐NaOH [pH 7.4], 1% v/v Nonidet P‐40, 0.5% w/v sodium deoxycholate, 150 mmol L −1 NaCl, and 4 mmol L −1 EDTA) with Complete Mini and PhosSTOP (both Roche Diagnostics).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mazumdar et al identified dual specificity phosphatase 4 (DUSP4) as the most commonly underexpressed protein phosphatase in ER-negative breast cancers, and showed that ectopic expression of DUSP4 inhibits the growth and invasive properties of ER-negative breast cancer cells by dephosphorylating growth promoting signaling proteins (13). Similarly, loss of DUSP4 promotes the progression of intraepithelial neoplasms into invasive carcinoma in the pancreas (14). Moreover, loss of DUSP4 activates the activation of MAPK pathway, thereby promoting a stem cell-like phenotype and dampening the response to neo-adjuvant therapy in breast cancer (15,16).…”
Section: Phosphatases As Tumor Suppressorsmentioning
confidence: 99%
“…9). In physiologic conditions, the transcription of DUSP4 is MEK-dependent and its expression in turn suppresses ERK, along with p38, JNK1, NF-kB, and Rb (9)(10)(11)(12), ensuring a proper negative feedback control of cellular proliferative stimuli. DUSP4 is differentially expressed among luminal and basal breast cancers.…”
Section: Introductionmentioning
confidence: 99%